Long non‐coding RNAs: Promising new targets in pulmonary fibrosis. (11th February 2021) - Zhang, Songzi; Chen, Hongbin; Yue, Dayong; Blackwell, Timothy S.; Lv, Changjun; Song, Xiaodong
Abstract: Pulmonary fibrosis is characterized by progressive and irreversible scarring in the lungs with poor prognosis and treatment. It is caused by various factors, including environmental and occupational exposures, and some rheumatic immune diseases. Even the rapid global spread of the COVID‐19 pandemic can also cause pulmonary fibrosis with a high probability. Functions attributed to long non‐coding RNAs (lncRNAs) make them highly attractive diagnostic and therapeutic targets in fibroproliferative diseases. Therefore, an understanding of the specific mechanisms by which lncRNAs regulate pulmonary fibrotic pathogenesis is urgently needed to identify new possibilities for therapy. In this review, we focus on the molecular mechanisms and implications of lncRNAs targeted protein‐coding and non‐coding genes during pulmonary fibrogenesis, and systematically analyze the communication of lncRNAs with various types of RNAs, including microRNA, circular RNA and mRNA. Finally, we propose the potential approach of lncRNA‐based diagnosis and therapy for pulmonary fibrosis. We hope that understanding these interactions between protein‐coding and non‐coding genes will contribute to the development of lncRNA‐based clinical applications for pulmonary fibrosis. Abstract : Different non‐coding RNAs (lncRNAs) exhibit different regulatory mechanisms because of their cellular localization, which, in turn, leads to their functional divergence in disease occurrence and progression. This review highlights how lncRNAs contribute to pulmonary fibrogenesis.